Liquid phase separation in AlCrFeNiMo0.3 high-entropy alloy. (September 2019) - Munitz, A.; Edry, I.; Brosh, E.; Derimow, N.; MacDonald, B.E.; Lavernia, E.J.; Abbaschian, R.
Abstract: Buttons of arc melted AlCrFeNiMo0.3 high-entropy alloy were characterized in the as-cast state using differential scanning calorimetry (DSC), X-ray diffraction (XRD), and scanning electron microscopy (SEM). The macrostructure of the arc-melted AlCrFeNiMo0.3 alloy consisted of two regions with different compositions: A top layer of AlNi-rich dendritic microstructure composed of a cellular dendrite core (DC) with a CrFeMo-rich rim and AlNi-rich interior, followed by radiating lamellar microstructure with the same phases at the interdendritic regions (ID). In contrast, the bottom region which is Cr, Fe, and Mo-rich consisted of dendrite elements, spheres, followed by a cellular microstructure with radiating lamellae similar to that observed in the top layer. The presence of two regions with different compositions is indicative of a stable liquid phase separation (LPS). In addition, the presence of spheres in the microstructure in the bottom region with different composition from that of the matrix is indicative of secondary LPS. We attributed the LPS in AlCrFeNiMo0.3 alloy to the significantly more attractive interaction between Al–Ni than that of the other binary combinations. Thermodynamic calculations were carried out on the alloy using SSOL5 and TCHEA thermodynamic databases. The thermodynamic calculation results indicate that the first phase to solidify is the disordered CrFeMo-rich BCC. Upon further cooling, a spinodal decomposition reaction forming disordered BCC (CrFeMo) and precipitates of ordered AlNi BCC B2 phase is accompanied with the formation of an FCC L12 phase. However, the calculations did not yield predictions of stable LPS; instead a very low-lying metastable LPS was predicted. Highlights: Stable liquid phase separation, LPS, was found in AlCrFeNiMo0.3 creating AlNi-rich liquid and Cr, Fe, and Mo-rich liquid. Usually LPS was found for alloys containing Cu due to the positive interaction of Cu with at least one of the other elements. Both LPS mechanisms reported: the thermally activated and constitutional LPS, are not applicable for AlCrFeNiMo0.3 . The significantly more attractive interaction between Al–Ni than that of the other binaries is the source of the LPS.